Analisa Perbandingan Penggunaan Bekisting Konvensional dengan Pra Cetak pada Pekerjaan Kolom Apartemen Begawan Malang - Aek, Paskalis; Suhudi; Wijaya , Handika Setya (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2019)
Technology in the world of construction is growing rapidly marked by the emergence of various new innovations, both in terms of equipment, materials, and methods of implementation. One of the construction work that has new innovations is formwork work. At present various kinds of materials with better quality have started to be used for construction work, especially for formwork material for high rise building project work. This requires an analysis of the type of formwork material that will be used. The results of the analysis of the calculation of the cost of formwork for column work in the construction of Begawan Apartment Malang Area GWT (Ground Water Tank) using pre-cast formwork is cheaper or 4% smaller than the use of conventional formwork material. For the total cost of column formwork using pre-printed Rp. 5.687.529,50, using conventional formwork in the amount of Rp.27.316.805,67 and the difference in both of them in the amount of Rp.22.629.276,17. From the analysis of observations of conventional and preprinted formwork time, it can be seen that conventional formwork time has 18 days while conventional formwork work has 12 days.